CONSTITUTIONAL CONCEPT OF LITHUANIAN INDEPENDECE ACT OF FEBRUARY 16, 1918 - Vaičaitis, Vaidotas A.; Paužaitė-Kulvinskienė, Jurgita (Teisė, 2015)
February 16, 1918 Lithuanian independence act has received too little attention from Lithuanian legal science so far, but hopefully this situation might be improved appoaching centenary anniversary of this document. It might be said that this Indpendence act might be considered as certain Lithuanian archetype act laying foundations for all contemporary Lithuanian legal and constitutional system. Nevertheless, this act rarely was analyzed in the context of Lithuanian constitutional traditions, therefore, the author of this article tries to fill up this gap, analysing it not only as constitutional, but even as certain supra-constitutional act. Analysing the content of the 1918 Indpendence act from constitutional point of view, might help us to find three constitutional provisions (clauses) in it as follows: constituent independence clause, international law clause and democracy clause. Therefore, all these three constitutional values let us consider the Act as part of the Lithuanian constitutional traditions. The article also shows certain historic hermeneutics of the 1918 Independence act, starting with so called Vilnius Conference decisions (1917) and finally ending with independence and republican resolution of Lithuanian Constituent Assembly (Steigiamasis Seimas) of May 15, 1920. The article finally ends with certain conclusions reflecting the very content of this analysis.